2015
DOI: 10.1074/mcp.m114.046904
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Components Define Protein Location to Membrane Microdomains*

Abstract: The plasma membrane is an important compartment that undergoes dynamic changes in composition upon external or internal stimuli. The dynamic subcompartmentation of proteins in ordered low-density (DRM) and disordered high-density (DSM) membrane phases is hypothesized to require interactions with cytoskeletal components. Here, we systematically analyzed the effects of actin or tubulin disruption on the distribution of proteins between membrane density phases. We used a proteomic screen to identify candidate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 90 publications
(107 reference statements)
0
50
1
Order By: Relevance
“…As a result, polar auxin transport is drastically reduced in abcb1 abcb19 and twd1, leading to widely overlapping phenotypes, including dwarfism, disoriented growth, and helical rotation (twisting) of epidermal layers (Geisler et al, 2003;Wu et al, 2010;Wang et al, 2013). Epidermal twisting in twd1/fkbp42 is in contrast to mutations of tubulin subunits, such as the rice (Oryza sativa) mutant twisted dwarf1 (Szymanski et al, 2015), nonhanded. The chaperone function of TWD1/FKBP42 is in functional analogy with the closest mammalian ortholog, FKBP38, shown to chaperone ABCC7/CFTR to the PM (Banasavadi-Siddegowda et al, 2011), but underlying mechanisms are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, polar auxin transport is drastically reduced in abcb1 abcb19 and twd1, leading to widely overlapping phenotypes, including dwarfism, disoriented growth, and helical rotation (twisting) of epidermal layers (Geisler et al, 2003;Wu et al, 2010;Wang et al, 2013). Epidermal twisting in twd1/fkbp42 is in contrast to mutations of tubulin subunits, such as the rice (Oryza sativa) mutant twisted dwarf1 (Szymanski et al, 2015), nonhanded. The chaperone function of TWD1/FKBP42 is in functional analogy with the closest mammalian ortholog, FKBP38, shown to chaperone ABCC7/CFTR to the PM (Banasavadi-Siddegowda et al, 2011), but underlying mechanisms are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Szymanski et al (2015) recently demonstrated that actin filaments are related to the formation and dynamics of microdomains and that microtubules regulate the amounts of microdomain proteins by observation of microdomain marker proteins such as Remorin1.2 during deletion of actin filaments or microtubules. Therefore, the proper organization of PM microdomains would need not only lipids such as sphingolipids but also proteins, especially cytoskeleton.…”
Section: Importance Of Pm Microdomain Organization By 2-hydroxy Sphinmentioning
confidence: 99%
“…In addition there is only an estimated one third of Arabidopsis plasma membrane proteins reported to exhibit strong sterol-dependencies [5] a basic requirement of proteins for possible raft-associations [11]. In plants associations of plasma membrane proteins or whole protein assemblies with stabilizing structures could therefore overcome decreased sterol levels by, for example, interactions or stabilization with the cytoskeleton [7]. There were less cytoskeletal proteins found in sterol-rich membrane domains in plants compared to those found in animal plasma membrane preparations; at the same time plant cell wall proteins made up the biggest functional group of proteins identified as responding to methyl-ß-cyclodextrin [5].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that almost all of the 16 remorin proteins known in Arabidopsis thaliana localize to (different) membrane microdomain platforms [2]. Concerning physiological roles of sterol-and sphingolipid-enriched compartments it was demonstrated in Arabidopsis that regulatory protein-protein interactions occur therein, as shown for the CPK21-mediated activation of the ion channel SLAH3 [7]. It is now established that sterols [8] and sterol-protein interactions play a role in the compartmentalization of plasma membrane proteins in plants and that these interactions play regulatory roles [9].…”
Section: Introductionmentioning
confidence: 99%